Manufacture of Bilayered Composite Hydrogels with Strong, Elastic, and Tough Properties for Osteochondral Repair Applications - Hui Yao; Congcong Wang; Yuchen Zhang; Ying Wan; Qing Min (Biomimetics, 2023)
Layered composite hydrogels have been considered attractive materials for use in osteochondral repair and regeneration. These hydrogel materials should be mechanically strong, elastic, and tough besides fulfilling some basic requirements such as biocompatibility and biodegradability. A novel type of bilayered composite hydrogel with multi-network structures and well-defined injectability was thus developed for osteochondral tissue engineering using chitosan (CH), hyaluronic acid (HA), silk fibroin (SF), CH nanoparticles (NPs), and amino-functionalized mesoporous bioglass (ABG) NPs. CH was combined with HA and CH NPs to build the chondral phase of the bilayered hydrogel, and CH, SF, and ABG NPs were used together to construct the subchondral phase of the bilayer hydrogel. Rheological measurements showed that the optimally achieved gels assigned to the chondral and subchondral layers had their elastic moduli of around 6.5 and 9.9 kPa, respectively, with elastic modulus/viscous modulus ratios higher than 36, indicating that they behaved like strong gels. Compressive measurements further demonstrated that the bilayered hydrogel with an optimally formulated composition had strong, elastic, and tough characteristics. Cell culture revealed that the bilayered hydrogel had the capacity to support the in-growth of chondrocytes in the chondral phase and osteoblasts in the subchondral phase. Results suggest that the bilayered composite hydrogel can act as an injective biomaterial for osteochondral repair applications.